Stress and burnout experienced by intercollegiate swimming head coaches - Pearson, R. T.; Baghurst, T.; Mwavita, M. (International Sport Coaching Journal, 2021)
The purpose of the present study was to investigate stress and burnout among intercollegiate head swimming coaches in the National Collegiate Athletic Association (NCAA). Participants were 223 coaches working at NCAA institutions who completed the Coaching Issues Survey, which measures potential stressors experienced by coaches using four subscales of Win-Loss, Time-Role, Program-Success, and Athlete-Concerns. Time-Role was the most significant stressor and Win-Loss the lowest. Females reported significantly higher stress levels than their male counterparts, t(197)=-2.87, p=.01, on all subscales. Overall, levels of stress were not significant by NCAA divisions I, II, and III F(2,201)=1.25, p=.29, suggesting that coaches across all levels experience stress. Findings highlight the importance of monitoring work-life balance across all collegiate athletic divisions and the need to understand why females report higher levels of stress and how this can be improved. Future research should consider how burnout can be avoided through coaching education and training interventions that might aid coaches who perceive their work environment as stressful.